Magnetic Fabric and Rockmagnetic Properties of the Archaean Granites from part of the Hyderabad Granitic Region (HGR), Eastern Dharwar Craton, India - Goutham, M. R.; Sandhya, R.; Patil, S. K.; Rao, B. Madhusudhan; Murthy, B. V. S. (My University, 2016)
Archaean granite samples, collected from unweathered basement from part of the Hyderabad Granitic Region (HGR) consisting of pink and grey varieties, are studied for their magnetic fabric and rock magnetic characters. Rock magnetic properties show wide range of characters for both the varieties and grey granite is found to be more magnetic than the pink variety. Average values of Natural Remanent Magnetization (NRM) intensity, Magnetic Susceptibility (K) and Koenigsberger’s ratio (Qn) are found to be 488 and 637 Am-1; 1689 and 1780; and 9 and 19.7 for pink and grey granites respectively. There are significant differences in the rock magnetic properties between the pink and grey granites such as NRM Intensity, magnetic susceptibility (K) and Qn. Probably this is an expression of grade of metamorphism that these rocks have undergone and thus may be attributed to the time difference in their formation. The magnetic mineralogy of the granites of the study area is dominated by multi domain magnetite as revealed by the Isothermal Remanent Magnetic (IRM) and thermo magnetic studies. Further, the fabric of the magnetic minerals shown by both pink and grey granites is similar. This indicates that the deformation recorded in these rocks is a wide spread, post-formational event in the Eastern Dharwar Craton (EDC) and is exactly preserved in the Hyderabad Granitic Region (HGR).
Keywords: Natural remanent Magnetisation; Anisotropy of Magnetic Susceptibility; Koenigsberger`s ratio; Isothermal Remanent magnetization; Thermo magnetism; Dharwar Craton; Hyderabad Granitic Region